If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 2s = 3s + -7 Reorder the terms: 4 + 2s = -7 + 3s Solving 4 + 2s = -7 + 3s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-3s' to each side of the equation. 4 + 2s + -3s = -7 + 3s + -3s Combine like terms: 2s + -3s = -1s 4 + -1s = -7 + 3s + -3s Combine like terms: 3s + -3s = 0 4 + -1s = -7 + 0 4 + -1s = -7 Add '-4' to each side of the equation. 4 + -4 + -1s = -7 + -4 Combine like terms: 4 + -4 = 0 0 + -1s = -7 + -4 -1s = -7 + -4 Combine like terms: -7 + -4 = -11 -1s = -11 Divide each side by '-1'. s = 11 Simplifying s = 11
| x^2+4x+18=40 | | 3x^2+23=-13 | | 7n-16n+4=0 | | -a+7(1+3a)-20=0 | | 2x+40=.182x | | 18x+3=10x-45 | | -(m-6)=3m+4 | | x^2+4x-18=40 | | 6x+8-2=-24 | | 12/m-3 | | -5x+16+-8(x+1)=6x | | 2x^2-3y^2=12 | | 4m/m-3 | | -3+7=-5 | | -6x-x+10=15-7x | | 1-n-5+16=-n-2n | | (9v+36)(v^2-6v+5)=0 | | -(x+7)-6=-20+6x | | N^2+16=-8n | | 3[4x-5(y-2)]= | | -3x-1=x-17 | | -5=9+4 | | X+4(x+2)=12 | | -2(9+4s)=34 | | 5a^2= | | 3a+12=6a+7 | | 4x^3-6x-6=0 | | -7(1-5h)=21 | | 3x+2y+2x+5z+7y+2z= | | 5x+13y=11 | | 3x(4)=180 | | 4.5(6.2)=n |